Electrochemical properties of heat-treated platinized titanium - Kasian, O. I.; Luk'Yanenko, T. V.; Velichenko, A. B. (Protection of Metals and Physical Chemistry of Surfaces, 2013)
The physicochemical properties and electrochemical behavior of platinized titanium anodes produced by a combined electrochemical method, which involves electrodeposition of a thin platinum layer on a titanium substrate followed by heat treatment, are studied. The process is shown to result in the appearance of a composite coating with a substantial content of titanium oxides. The composite obtained is an n-type semiconductor, the flat-band potentials of which and the number of charge carriers depend on the preparation conditions. It is proposed to use the reduction peak of oxygen-containing platinum compounds on the stripping voltammogram as a correlation parameter for predicting the electrocatalytic activity of heat-treated Ti/Pt composite electrodes with respect to the oxygen evolution reaction. © 2013 Pleiades Publishing, Ltd.
CRIS-Team Scopus Importer:2023-03-07